A Holistic Approach to Working Conditions Quality Management Model - Rafał MIERZWIAK (Communications of International Proceedings, 2022)
This paper aims at systematising factors influencing the quality of working conditions in enterprises. The conducted theoretical and practical research allowed for formulating a comprehensive model of the quality of working conditions, in which the determinants of the quality of working conditions were identified and the relationship between them and their impact on the business aspects of the functioning of enterprises was determined. The paper consists of five sections. Section (1) presents the basic issues related to managing the quality of working conditions and presents the general structure of the management model for this enterprise operation area. Section (2) discusses the management of the quality of working conditions at the normative level. Then, Section (3) shows the links between the quality of working conditions and the strategic approach in management. Subsequently, section (4) presents the factors that influence the operational aspect of managing the quality of working conditions. Finally, Section (5) provides a summary and synthesis of the problems discussed in the article.
Keywords: quality of working conditions; management of working conditions; holistic approach to the design of working conditions; ergonomics and safety at work